Answer

Verified

52.2k+ views

**Hint:**Use the formula of Arithmetic progression sequence for the nth terms that is \[{a_n} = a + \left( {n - 1} \right)d\] where, a initial term of the AP and d is the common difference of successive numbers. Calculate the value of a. We use the formula of the sum of n terms in Arithmetic progression that is \[{S_n} = \dfrac{n}{2}\left[ {2a + \left( {n - 1} \right)d} \right]\]. Calculate the sum of the AP, \[{S_n}\].

**Complete step by step solution:**

**Given data:**The ${22^{nd}}$ term that is given for an arithmetic progression is 149.

Common difference is \[d = 7\]

Now, we know about the Arithmetic progression sequence for the nth terms is given by the following expression:

\[{a_n} = a + \left( {n - 1} \right)d\]

Here, the first term of the arithmetic progression sequence is $a$.

Now, calculate the value of $a$. Substitute the value of d = 7,n = 22 and ${a_n} = 149$ in \[{a_n} = a + \left( {n - 1} \right)d\].

149 = a + (22- 1)7

149 = a + 147

a = 149 - 147

= 2

Now, we know about the formula of the sum of n terms in Arithmetic progression is given by the following expression:

\[{S_n} = \dfrac{n}{2}\left[ {2a + \left( {n - 1} \right)d} \right]\]

Simplify the above equation by substituting \[{a_n} = a + \left( {n - 1} \right)d\].

\[{S_n} = \dfrac{n}{2}\left[ {a + {a_n}} \right]\]

Now, calculate the value of ${S_n}$ by substituting $n = 23$, $a = 2$ and $a_n = 149$ in the expression for the sum of the Arithmetic progression \[{S_n} = \dfrac{n}{2}\left[ {a + {a_n}} \right]\].

${S_{22}} = \dfrac{{22}}{2}\left[ {2 + 149} \right]\\

= 11\left[ {151} \right]\\

= 1,661

$

**Hence, the sum of the first 22 terms of an Arithmetic progression is \[{S_{22}} = 1,661\].**

**Note:**The general equation of the Arithmetic progression is \[a,a + d,a + 2d,a + 3d,...\], where a is initial term of the AP and d is the common difference of successive numbers. Make sure use the formula of the sum of n terms in Arithmetic progression that is \[{S_n} = \dfrac{n}{2}\left[ {2a + \left( {n - 1} \right)d} \right]\] and use the Arithmetic progression sequence for the nth terms that is \[{a_n} = a + \left( {n - 1} \right)d\].

Recently Updated Pages

In a family each daughter has the same number of brothers class 10 maths JEE_Main

If 81 is the discriminant of 2x2 + 5x k 0 then the class 10 maths JEE_Main

What is the value of cos 2Aleft 3 4cos 2A right2 + class 10 maths JEE_Main

If left dfracleft 2sinalpha rightleft 1 + cosalpha class 10 maths JEE_Main

The circumference of the base of a 24 m high conical class 10 maths JEE_Main

From the top of a hill h meters high the angles of class 10 maths JEE_Main

Other Pages

The resultant of vec A and vec B is perpendicular to class 11 physics JEE_Main

Which of the following sets of displacements might class 11 physics JEE_Main

If a wire of resistance R is stretched to double of class 12 physics JEE_Main

Electric field due to uniformly charged sphere class 12 physics JEE_Main

Explain the construction and working of a GeigerMuller class 12 physics JEE_Main

Differentiate between homogeneous and heterogeneous class 12 chemistry JEE_Main